Policy Implementation of Food Security Program in North Minahasa Regency - Katuuk, Bertha Loutje; Kairupan, Sisca B.; Tarore, Steven Vleike (Technium Social Sciences Journal, 2025)
This study aims to find out, analyze and describe the Food Security Program Policy in the rice sector as well as the determinant factors in achieving food security in the rice sector in North Minahasa Regency with a focus on the main indicators, namely rice availability, rice production, rice access and rice price stability. The research used a qualitative approach with a descriptive method, through in-depth interviews with the Food Service Office, farmers, and the community, as well as document review related to regional food security policies. The results show that the availability of rice in North Minahasa Regency is good and stable, characterized by surplus stocks in the first quarter of 2025. Rice production has increased thanks to government assistance in the form of superior seeds, subsidized fertilizers, training, and agricultural tools. However, production is still constrained by land shrinkage, erratic weather, and limited irrigation. Access to rice in mainland areas is considered quite good, but island areas still face distribution barriers due to lack of infrastructure and sea transportation. Determinant factors affecting food security, particularly in the aspects of rice production and access, include agricultural land area, weather and irrigation conditions, distribution infrastructure, people's purchasing power, and local government policies. Based on these findings, it is recommended that the government strengthen the protection of agricultural land, improve distribution infrastructure, especially in remote areas, expand the scope of cheap food programs, and encourage the use of adaptive agricultural technology. Future research is recommended to use a quantitative approach or a comparative study between regions to expand the scope of the analysis.